2019
DOI: 10.1093/eurheartj/ehz025
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms linking preterm birth to onset of cardiovascular disease later in adulthood

Abstract: Cardiovascular disease (CVD) rates in adulthood are high in premature infants; unfortunately, the underlying mechanisms are not well defined. In this review, we discuss potential pathways that could lead to CVD in premature babies. Studies show intense oxidant stress and inflammation at tissue levels in these neonates. Alterations in lipid profile, foetal epigenomics, and gut microbiota in these infants may also underlie the development of CVD. Recently, probiotic bacteria, such as the mucin-degrading bacteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 81 publications
0
43
0
2
Order By: Relevance
“…Results of β-diversity of intestinal microbiota reflected by PCA revealed that specific diet and treatment regimens promoted major alterations in the gut microbiota and gut microbial-host related co-metabolites in mice. Furthermore, HFD significantly changed the structure of the community dynamics resulting in decreased abundance of Akkermansia, which is commonly recognized as a beneficial bacterium that is negatively associated with inflammation in the body (Bavineni et al, 2019). Further, Akkermansia supplementation alleviates obesity, inflammatory response in diabetic patients, insulin resistance, glucose tolerance, and other adverse symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Results of β-diversity of intestinal microbiota reflected by PCA revealed that specific diet and treatment regimens promoted major alterations in the gut microbiota and gut microbial-host related co-metabolites in mice. Furthermore, HFD significantly changed the structure of the community dynamics resulting in decreased abundance of Akkermansia, which is commonly recognized as a beneficial bacterium that is negatively associated with inflammation in the body (Bavineni et al, 2019). Further, Akkermansia supplementation alleviates obesity, inflammatory response in diabetic patients, insulin resistance, glucose tolerance, and other adverse symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, other available data speculate that neonatal colonization contributes to other short- and long-term sequelae of prematurity, such as respiratory distress and bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP) [67], somatic growth in early life, and cardiovascular and other non-communicable chronic diseases later in adulthood [68,69,70].…”
Section: Neonatal Dysbiosis and Consequences For The Premature Infmentioning
confidence: 99%
“…Epigenetic modifications refer to dynamic and heritable changes in gene expression without DNA sequence changes. These are profoundly involved in OS responses [ 99 ] and are regarded as potential mechanisms that influence the developmental origins of CVDs later in adulthood [ 100 ]. Maximal epigenetic reprogramming, characterized as ’dynamic’, ’extremely sensitive’, and ’plastic’, occurs during the early stages of life, coinciding with the time that ART procedures take place [ 101 , 102 ].…”
Section: Os-associated Mechanisms In Artmentioning
confidence: 99%
“…From the maternal point of view, advanced maternal age (AMA) [ 154 , 155 ] and OS-increased ART-associated pregnancy complications (e.g., HDP [ 156 , 157 ], GDM [ 158 ], IUGR [ 159 ], and preterm birth [ 100 ]) are frequently associated with cardiovascular dysfunction in the offspring. For example, AMA/HDP/IUGR have been linked with increased blood pressure and/or altered cardiovascular function in offspring [ 154 , 155 , 156 , 159 ], while GDM/preterm birth have been linked with CVDs in offspring [ 100 , 158 ]. Specifically, in a mouse model, it was reported that AMA affects the phenotype of the offspring in a sex-dependent manner: in young adulthood (four months of age), male (but not female) offspring birthed by aged dams presented reperfusion injury and impaired endothelium-dependent relaxation.…”
Section: Long-lasting Cardiovascular Effectsmentioning
confidence: 99%